2017
DOI: 10.1007/s10456-016-9538-1
|View full text |Cite
|
Sign up to set email alerts
|

A somatic GNA11 mutation is associated with extremity capillary malformation and overgrowth

Abstract: Background Capillary malformation is a cutaneous vascular anomaly that is present at birth, darkens over time, and can cause overgrowth of tissues beneath the stain. The lesion is caused by a somatic activating mutation in GNAQ. In a previous study we were unable to identify a GNAQ mutation in patients with a capillary malformation involving an overgrown lower extremity. We hypothesized that mutations in GNA11 or GNA14, genes closely related to GNAQ, also may cause capillary malformations. Methods Human capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 14 publications
(24 reference statements)
4
76
1
Order By: Relevance
“…Consistently with our findings, previous studies have reported that NR4A1 activation was noted in fatty liver disease and atherosclerosis [24,25] and that the genetic deletion of NR4A1 or pharmacological inhibition of NR4A1 retards or prevents the progression of nonalcoholic fatty liver and atherosclerosis [66,67]. Collectively, these observations have demonstrated the sufficiency of NR4A1 to exacerbate chronic metabolic diseases, which may highlight a new method for treating chronic metabolic disorders by targeting NR4A1.…”
Section: Discussionsupporting
confidence: 80%
“…Consistently with our findings, previous studies have reported that NR4A1 activation was noted in fatty liver disease and atherosclerosis [24,25] and that the genetic deletion of NR4A1 or pharmacological inhibition of NR4A1 retards or prevents the progression of nonalcoholic fatty liver and atherosclerosis [66,67]. Collectively, these observations have demonstrated the sufficiency of NR4A1 to exacerbate chronic metabolic diseases, which may highlight a new method for treating chronic metabolic disorders by targeting NR4A1.…”
Section: Discussionsupporting
confidence: 80%
“…) and GNA11 (Couto et al . ) in mediating angiogenesis. In addition, double knockdown of GNAq and 11 in HUVECs blocks VEGFA‐induced cell migration (Zeng et al .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Couto et al . () reported that a somatic mutation of GNA11 is associated with capillary malformation in human. These data suggest the importance of GNA11 with respect to mediating endothelial function, possibly depending on the origins of endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…The present study contains a risk of selection bias since only patients requiring excision were included. Somatic mutations in other genes, such as GNA11 , SMARCA4 , EPHA3 , MYB , PDGFR‐β , PIK3CA , and RASA1 , have been found in patients with capillary malformation; however mutations of those genes were not evaluated in this study Genetic assays for those genes might provide a clearer perspective on the genotype‐phenotype associations in capillary malformation and Sturge‐Weber syndrome.…”
Section: Discussionmentioning
confidence: 93%